Penyelesaian Sengketa Pemilihan Bupati Bengkulu Selatan di Mahkamah Konstitusi - Ni'matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2011)
Constitutional Court decision annulling Head of District of South Bengkulu and asking for re-election creates polemic in society. This research discusses: First, the competency of Constitutional Court annulling the election result of South Bengkulu; Second, the consistency of Constitutional Court decision in granting applicant’s request.This research is a normative research using case approach to see the basis of judge’s consideration in regional election dispute of South Bengkulu.This research concludes that: (a) Normatively, Constitutional Court has no competency in annulling regional election result, however because there is a juridical defect in the practice, Constitutional Court annul it; (b) There is inconsistency in Constitutional Court decision in deciding the winner of re-election after the Constitutional Court decision in regional election of South Bengkulu.